Konsep Peran Ibu dalam Pendidikan Anak Perspektif Tafsir Kontemporer: Analisis atas Surah Maryam - Bayu Mujrimin (Universitas Al Falah As Sunniyah Kencong Jember (UAS Press), 2026)
This study aims to explore the role of mothers in child education based on contemporary interpretations of Surah Maryam. Surah Maryam not only presents narratives of faith and monotheism but also showcases the exemplary figure of a mother, Maryam bint Imran, in nurturing noble values in her child, Prophet Isa (Jesus, peace be upon him). This qualitative research employs a library research method and a thematic exegesis approach to analyze Surah Maryam through contemporary tafsir works such as Tafsir al-Misbah (M. Quraish Shihab), Tafsir al-Munir (Wahbah az-Zuhaili), and Fi Zhilal al-Qur'an (Sayyid Qutb). The findings reveal that Maryam represents a mother with profound spiritual strength, emotional resilience, and moral commitment in educating her child. In the context of modern education, these values are highly relevant as a foundation for reinforcing the maternal role in character development. The study concludes that contemporary interpretations of Surah Maryam emphasize the critical role of mothers as the first and foremost educators in the family, particularly in instilling faith, patience, and responsibility. The implication of this study highlights the need to integrate Qur'anic values into family education as the cornerstone of children's character formation